2017
DOI: 10.3389/fonc.2017.00156
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Validity and Utility of Tumor-Infiltrating Lymphocytes in Routine Clinical Practice for Breast Cancer Patients: Current and Future Directions

Abstract: The interest in tumor-infiltrating lymphocytes (TILs) as a prognostic biomarker in breast cancer has grown in recent years. Biomarkers must undergo comprehensive evaluation in terms of analytical validity, clinical validity and clinical utility before they can be accepted as part of clinical practice. The International Immuno-Oncology Biomarker Working Group has developed a practice guideline on scoring TILs in breast cancer in order to standardize TIL assessment. The prognostic value of TILs as a biomarker in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
80
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(84 citation statements)
references
References 58 publications
4
80
0
Order By: Relevance
“…The mechanisms underlying antitumor immune responses have been extensively investigated through in vitro and in vivo experiments as well as through clinical studies (3,4). It has been reported that co-stimulatory molecules contribute to T-cell activation and improve antitumor immunity, thereby playing an important role in tumor diagnosis and treatment (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms underlying antitumor immune responses have been extensively investigated through in vitro and in vivo experiments as well as through clinical studies (3,4). It has been reported that co-stimulatory molecules contribute to T-cell activation and improve antitumor immunity, thereby playing an important role in tumor diagnosis and treatment (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…It has been established in several studies that tumor infiltrating lymphocytes in baseline, pretreatment biopsies of breast cancer are powerful prognostic markers of the clinical outcome in triple negative and HER2 positive breast cancers [11,12]. The correlation between posttreatment levels of TIL and clinical outcome is less clear, perhaps due to the fact that cases with pathological complete response are often eliminated from further analysis.…”
Section: Discussionmentioning
confidence: 99%
“…1), which account for about 11% of all invasive breast carcinomas [10]. TILs are more frequently observed in high-grade lesions, in TNBC and HER2-positive breast carcinomas [11][12][13]. In a recently reported cohort of breast carcinoma patients treated with neoadjuvant chemotherapy, TIL mean values for TNBCs, HER2-positive carcinomas and luminal carcinomas were reported as 28.5, 26.5 and 24%, respectively [14].…”
Section: Tumor-infiltrating Lymphocytesmentioning
confidence: 99%